Middle–Upper Jurassic palynology of the South Sallum well, North Western Desert, Egypt - Tarek F. Mostafa; Maher I. El Soughier; Walid A. Makled (Egyptian Journal of Petroleum)
Palynological analyses have been carried out on some samples of Middle–Upper Jurassic from the South Sallum well, North Western Desert, Egypt. A refinement of the original chronostratigraphy has been suggested and the stages of Bathonian – Callovian and the Callovian – Oxfordian are recognized. Two biozones were identified that are Dichadogonyaulax sellwoodi i – Wanaea acollaris – Wanaea digitata Assemblage Zone in the Bathonian – Callovian and Amphorula dodekovae Interval Zone in the Callovian – Oxfordian. Other important dinoflagellates and miospores of Middle–Upper Jurassic are recorded in the samples. The palaeoenvironmental settings are interpreted on the basis of statistical relative abundances of the palynomorphs, in the course of their ecological preferences. Depositional regime fluctuates between marginal marine to normal marine. A warm-humid climate prevails throughout the deposition, as indicated by the abundance of ferns, and other hygrophilous spores, and rare xerophytes. Keywords: Jurassic, Spores, Pollen, Dinoflagellate cysts, Palynostratigraphy, Palaeoecology, North Western Desert, Egypt